2016
DOI: 10.3382/ps/pew055
|View full text |Cite
|
Sign up to set email alerts
|

Effects of probiotics feeding on meat quality of chicken breast during postmortem storage

Abstract: This study evaluated the effects of dietary probiotic supplement and postmortem storage on meat quality of chicken breast during retail display. A total of 35 birds were randomly obtained from 3 feeding groups (control without probiotic supplement, 250 ppm Sporulin, and 500 ppm PoultryStar). The probiotic supplement had no influence on feed conversion ratio and body weight gain, as well as body weight at 29 and 44 d (P > 0.05). After slaughter, each side of the breast muscles (M. Pectoralis major) was assigned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 29 publications
2
34
3
1
Order By: Relevance
“…found that acute heat stress (35 °C for 2 h) did not affect the water‐holding capacity of chicken thigh meat, concluding that chicken thigh muscle may be less sensitive to oxidative damage induced by heat stress compared to breast muscle. In terms of the supplement effect of B. subtilis , previous studies mostly found no difference in water‐holding capacity of chicken breast muscle, although some positive effects have been also observed . The findings in the present study also indicate that heat stress and probiotic supplementation have no impact on water‐holding capacity of ground chicken leg meat during display, processing and cooking.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…found that acute heat stress (35 °C for 2 h) did not affect the water‐holding capacity of chicken thigh meat, concluding that chicken thigh muscle may be less sensitive to oxidative damage induced by heat stress compared to breast muscle. In terms of the supplement effect of B. subtilis , previous studies mostly found no difference in water‐holding capacity of chicken breast muscle, although some positive effects have been also observed . The findings in the present study also indicate that heat stress and probiotic supplementation have no impact on water‐holding capacity of ground chicken leg meat during display, processing and cooking.…”
Section: Resultssupporting
confidence: 59%
“…Similarly, Debut et al 36 reported that heat stress did not alter lightness, redness and yellowness of chicken thigh meat. In addition, previous studies noted that the feeding of B. subtilis alone or with other microbial species had no influence on the color characteristics of chicken breast muscle, 11,37,39,40,44 as well as leg muscle. 38,44 Hue angle of ground chicken leg meat marginally increased from 60.4 at day 0 to 61.4 at day 3 (P = 0.0378).…”
Section: Color Characteristicsmentioning
confidence: 92%
“…The leg muscles were characterised by lower water holding capacity and higher cooking loss. In turn, Kim et al (2016) reported no significant effect of the use of probiotic containing Enterococcus spp., Pediococcus spp., Bifidobacterium spp., and Lactobacillus spp. on the colour (attributes L à , a à , b à ), pH, and cooking loss of breast muscles from broiler chickens aged 45 days.…”
Section: Introductionmentioning
confidence: 93%
“…Moisture, crude protein, fat and ash contents were determined according to the procedure described by (AOAC) [13]. Water holding capacity (WHC) of chicken breasts was determined in duplicate according to the centrifugal method described by (Kim) [14]. The WHC (%) was estimated by calculating the percentage breast weight before and after centrifugation; WHC (%) = sample weight after centrifugation (g) sample weight befor centrifugation × 100…”
Section: Chemical and Physical Attributes Of Breast Meatmentioning
confidence: 99%